2008
DOI: 10.1039/b719767e
|View full text |Cite
|
Sign up to set email alerts
|

Urea derivatives are highly active catalysts for the base-mediated generation of terminal epoxides from aldehydes and trimethylsulfonium iodide

Abstract: N,N -Diarylureas have been shown to efficiently catalyse sulfonium ylide-mediated aldehyde epoxidation reactions for the first time. These processes are of broad scope and can be coupled with a subsequent Cu(II) ion-catalysed Meinwald rearrangement to give an efficient and convenient protocol for aldehyde homologation without intermediate purification.Epoxides are among the most versatile and useful synthetic building blocks available to the organic chemist. One of the most straightforward non-oxidative method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(9 citation statements)
references
References 63 publications
1
8
0
Order By: Relevance
“…Reasoning, therefore, that (thio)urea derivatives could stabilise the developing negative charge on the oxygen heteroatom in the rate-determining 34 addition step (see 26, Scheme 5) transition state of the CoreyChaykovsky reaction, we set out to evaluate the influence of a range of (thio)urea catalysts in the synthesis of styrene oxide from benzaldehyde under biphasic conditions. 35 Selected results from this study are outlined in Table 3: in the absence of catalyst, no reaction was detected after 24 hours. While urea and thiourea were inactive, N,N¢-diaryl analogues with electron-deficient aromatic substituents promoted the reaction at 5 mol% levels.…”
Section: Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…Reasoning, therefore, that (thio)urea derivatives could stabilise the developing negative charge on the oxygen heteroatom in the rate-determining 34 addition step (see 26, Scheme 5) transition state of the CoreyChaykovsky reaction, we set out to evaluate the influence of a range of (thio)urea catalysts in the synthesis of styrene oxide from benzaldehyde under biphasic conditions. 35 Selected results from this study are outlined in Table 3: in the absence of catalyst, no reaction was detected after 24 hours. While urea and thiourea were inactive, N,N¢-diaryl analogues with electron-deficient aromatic substituents promoted the reaction at 5 mol% levels.…”
Section: Methodsmentioning
confidence: 95%
“…To examine the validity of this hypothesis we evaluated the (thio)ureas shown in Table 5 as catalysts of the hitherto unknown organocatalytic reduction of benzil (34) to benzoin (35) in conjunction with catalytic amounts of Nbenzylnicotinamide (BNA) as the hydride donor in the presence of sodium dithionite. A range of control experiments where one of the two catalytic reaction components was removed demonstrated that significant levels of reduction occurred only when the BNA (which is reduced in situ by the dithionite) and the (thio)urea catalyst were present together (Table 5, entries 1-7).…”
Section: Organocatalytic Reduction Of Ketonesmentioning
confidence: 99%
“…This receptor might exist in the syn – syn conformation due to intramolecular interactions between acidic aromatic C–H groups and the sulfur atom as observed for some thiourea molecules 13. Finally, a bifunctional hybrid amide/ N ‐acylsulfonamide 7 was prepared incorporating both increased hydrogen bond donating properties and also the possibility to deprotonate the sulfonyl N–H; a potentially useful feature where proton transfer may occur and/or where activation of an electrophile plays a key role in the catalytic cycle 17,18. In this paper, we report the synthesis, comparative anion binding properties, X‐ray structure of 5 and preliminary catalytic and kinetic results in the Baylis–Hillman reaction 19…”
Section: Resultsmentioning
confidence: 99%
“…Based on these remarks, two very simple ureas 4k and 4l were prepared and assayed as BACE-1 inhibitors. 1,3-Bis(3,5-Bis(trifluoromethyl)phenyl)urea, 4k is well known in the field of organocatalysis [42][43][44][45][46][47][48][49][50] . The two N-H are highly acidic and equivalent in 4k.…”
Section: Resultsmentioning
confidence: 99%